D-brane instantons in type II orientifolds - Blumenhagen, Ralph; Weigand, Timo (Annual review of nuclear and particle science, 2009)
We review recent progress in determining the effects of d-brane instantons in supersymmetric compactifications of Type II string theory to four dimensions. We describe the abstract d-brane instanton calculus for holomorphic couplings such as the superpotential, the gauge kinetic function, and higher fermionic F-terms, and we briefly discuss the implications of background fluxes for the instanton sector. We then summarize the concrete consequences of stringy d-brane instantons for the construction of semirealistic models of particle physics or supersymmetry breaking in compact and noncompact geometries.
Gesehen am 09.01.2018